Determinant Factors of Stunting among Toddlers Based on Birth History, Exclusive Breastfeeding, Supplementary Feeding, and Maternal Height Status - Dahliansyah Dahliansyah; Desi Desi; Ayu Rafiony; Ismi Trihardiani (MEDICA (International Medical Scientific Journal), 2026)
Stunting is a chronic nutritional problem that remains a public health priority in Indonesia, including in West Kalimantan Province and the city of Pontianak, where prevalence rates are still above the national average. This condition is influenced by various prenatal, perinatal, and postnatal factors, necessitating a comprehensive analysis of its determinants at the local level. This study aimed to analyze the relationship between birth history (birth weight and birth length), exclusive breastfeeding, complementary feeding (PMT), and maternal height with the incidence of stunting among toddlers in South Pontianak in 2024. This study employed an analytical observational design with a cross-sectional approach, involving 1.000 toddlers selected through stratified random sampling, and data were analyzed using Chi-Square and logistic regression tests. The results showed that birth weight (p=0.002), birth length (p=0.002), PMT (p=0.003), and maternal height (p=0.016) were significantly associated with stunting, where low birth weight increased the risk by 1.8 times, short birth length by 1.55 times, and maternal height <150 cm by 1.4 times, while PMT acted as a protective factor (OR=0.62) despite a higher prevalence of stunting among recipients; exclusive breastfeeding was not significantly associated (p=0.471). In conclusion, stunting is influenced by prenatal and maternal factors, highlighting the importance of strengthening maternal nutrition, early growth monitoring, and optimizing targeted supplementary feeding programs (PMT) as key strategies for prevention.